The Effect of the Fishbowl Technique Implementation on Studentsʹ Speaking Skills for Twelve-Grade Students at Senior High School - Lili Antika; Sigit Suharjono (Universitas Islam Negeri Palopo, 2025)
This study investigated the effect of the Fishbowl Technique on the speaking skills of twelve-grade students at SMAN 2 Kotabumi, focusing on the problem of students' low speaking skills and high speaking anxiety. A quantitative methodology using a Quasi-experimental Design was used, with 68 students selected as participants (34 in the experimental group and 34 in the control group). Data were obtained through speaking assessments (pre-test and post-test) and analyzed through Independent Samples T-Test. The findings revealed a statistically significant difference in the post-test mean scores between the two. This result was reinforced by the calculated t-value (6.85), which was significant at p < 0.05. In addition, this study showed a strong effect, confirmed by the N-Gain score of 0.565 in the experimental group, which is classified as moderate effectiveness, compared to the N-Gain of 0.079 in the control group. This study concluded that the Fishbowl Technique is an effective and appropriate technique for improving students' speaking skills.